2020
DOI: 10.1016/j.sleep.2019.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The McGill score as a screening test for obstructive sleep disordered breathing in children with co-morbidities

Abstract: Please cite this article as: Trucco F, Rosenthal M, Bush A, Tan H-L, The McGill score as a screening test for obstructive sleep disordered breathing in children with co-morbidities, Sleep Medicine,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Interestingly, a recent study suggests that the positive predictive value of the MOS may be lower in this group due to non-obstructive conditions causing desaturations. [20] The lower time threshold required to score nocturnal pulse oximetry tracings has been taken as 6 hours. [4] It has been recognised that further work needs to be done to determine the minimum recorded sleep time for children.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study suggests that the positive predictive value of the MOS may be lower in this group due to non-obstructive conditions causing desaturations. [20] The lower time threshold required to score nocturnal pulse oximetry tracings has been taken as 6 hours. [4] It has been recognised that further work needs to be done to determine the minimum recorded sleep time for children.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, professional associations such as the American Academy of Pediatrics, American Academy of Sleep Medicine, American Academy of Otolaryngology-Head and Neck Surgery Foundation, European Respiratory Society, have further suggested that in the presence of characteristic OSA symptoms and some supportive physical findings, implementation of simplified testing procedures could replace the gold standard PSG in the form of home-based multichannel respiratory recordings or even single channel overnight oximetry. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 We have been among the latter, particularly based on the concern of limited access to PSG testing for children along with excessive financial costs. Development of such validated scalable diagnostic tools that can be automated would substantially reduce financial burden as well as time consuming labor involved in scoring and interpretation of polysomnograms.…”
Section: What Constitutes Mild Obstructive Sleep Apnea (Osa)?mentioning
confidence: 99%
“…Development of such validated scalable diagnostic tools that can be automated would substantially reduce financial burden as well as time consuming labor involved in scoring and interpretation of polysomnograms. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 Such approaches if adopted more universally, would result not only in expedited evaluation of many children who currently are required to wait for long periods of time before being diagnosed, but would also facilitate access to pediatric sleep laboratories for those children in whom the diagnosis is uncertain, or the clinical presentation is more complex and requires more sophisticated diagnostic approaches.…”
Section: What Constitutes Mild Obstructive Sleep Apnea (Osa)?mentioning
confidence: 99%
See 1 more Smart Citation
“…The McGill score is used worldwide as a screening tool to predict the presence and classify the severity of obstructive sleep apnea syndrome (OSAS) in children. Trucco et al (1) compared the McGill score to the results of cardiorespiratory polygraphy in 312 children, including 183 with an associated medical condition. Their results confirm previous data showing that the positive predictive value of the McGill score for OSAS is lower in children with an associated medical condition.…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%